Ecologization of Woodworking Industry as a Factor of Forest Biodiversity - Deyneko, Lyudmyla; Kyshnіrenko, Oksana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Ways to maintain the forest biodiversity in the context of woodworking industry development are explored in this paper. The purpose of this paper is to substantiate perspective ways of ecologization in woodworking industry, including conservation of resources, implementation of certification and ecological management systems that will not only facilitate economic effects, but will also constitute a precondition for saving the biodiversity of Ukrainian forests. An analysis of logging volumes during the latter years is made. Negative ecological externalities of logging increase are grounded, a loss of biodiversity – in particular. The authors consider as such externalities the following: loss of biodiversity during logging; replacement of primary forests by secondary ones that are not as productive; loss of raw wood during logging and woodworking; emission of harmful substances into the atmosphere through stationary pollution sources; creation of toxic waste; huge volumes of water consumption during production. The authors established that the main factor of woodworking enterprises’ influence over the environment is the loss of biodiversity. It leads to a shift in energetic and mass exchange in the biosphere that leads to a deterioration of ecological infrastructure of human living. In addition, it weakens resistance to negative climate change. Modernization of woodworking industry by resource-conserving and waste-free technologies of wood and biomass deep processing, as well as of recycling of products from wood and paper, will decrease the ecological pressure on forest resources and facilitate maintenance of the forest biodiversity. Perspective ways of ecologization in woodworking industry are proposed, based on the best practices of European countries. This will allow for the needs of woodworking industry to be balanced with the ecological capacities of Ukraine.